2017
DOI: 10.1007/s10354-017-0544-8
|View full text |Cite
|
Sign up to set email alerts
|

Body dysmorphic disorder: history and curiosities

Abstract: Body dysmorphic disorder is a chronic psychiatric disorder characterized by excessive preoccupation with an absent or minimal physical deformity. It causes severe distress and impairs normal functioning. In the last centuries, this disorder has been mentioned in the medical literature by important mental health practitioners by different names, such as "dysmorphophobia" or "dermatologic hypochondriasis". However, not until the last century was it included among the obsessive-compulsive disorders, although its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 11 publications
1
14
0
5
Order By: Relevance
“…Finally, the patient's preoccupation should not be accounted for by another mental illness, such as the dissatisfaction with body shape implied in anorexia nervosa (AN) 1 , 2 . In the DSM-V, published in 2013, 3 BDD was classified among obsessive-compulsive disorder (OCD) and related disorders, with the addition of the diagnostic criterion of repetitive behaviours such as excessive grooming, reassurance seeking, and mirror checking, or mental acts, including comparisons of the physical defect with that of other people 4 , 5 …”
Section: Introductionmentioning
confidence: 99%
“…Finally, the patient's preoccupation should not be accounted for by another mental illness, such as the dissatisfaction with body shape implied in anorexia nervosa (AN) 1 , 2 . In the DSM-V, published in 2013, 3 BDD was classified among obsessive-compulsive disorder (OCD) and related disorders, with the addition of the diagnostic criterion of repetitive behaviours such as excessive grooming, reassurance seeking, and mirror checking, or mental acts, including comparisons of the physical defect with that of other people 4 , 5 …”
Section: Introductionmentioning
confidence: 99%
“… 8 The unconscious displacement of inferiority and poor self-image has been reported to be a psychological etiological factor in BDD, and the young person’s experiences of bullying and negative evaluations by others during the primary school years support this association. 9 We also know that there is a positive family history in 5.8% of first-degree relatives suggesting that BDD could be familial and there is a likelihood that this association may hold true in the case we are reporting here, given the mother’s increased preoccupation wither physical appearance and history of cosmetic procedures. 10 …”
Section: Discussionmentioning
confidence: 59%
“…This outcome suggested, that being in discomfort with one's ideal body image and in struggle to accept the real body image leads to body dissatisfaction has negative consequences. In support of this, past evidence associates body image discrepancies (ideal vs. real) with a range of negative health outcomes such as depression and hypochondriasis (e.g., Cash and Smolak, 2011;Wilson et al, 2013;França et al, 2017;Becker et al, 2019). In addition, it seems plausible to assume that discrepancies between the real and the ideal body image, may lead to a state of cognitive dissonance, promoting internal discomfort and stress (Festinger, 1957;Dilakshini and Kumar, 2020).…”
Section: Discussionmentioning
confidence: 94%
“…Accordingly, it has been shown that body image is associated with psychosocial functioning (Cash and Fleming, 2002;Fatt et al, 2020). Many studies show that a negative body image is correlated with low self-esteem, depression, poor physical wellbeing, low quality of life and hypochondriasis (Cash and Smolak, 2011;Wilson et al, 2013;França et al, 2017;Becker et al, 2019), while a positive attitude is linked to high-levels of well-being, selfesteem, weight stability, self-care and physical activities as well as proactive coping behaviors (Cash and Fleming, 2002;Zanon et al, 2016;Swami et al, 2018;Sabiston et al, 2019).…”
Section: Introductionmentioning
confidence: 99%